870 Association of MGMT Methylation With Response to Chemotherapy in WHO Grade 2 Low Grade Glioma. (April 2023) - Chalif, Eric; Young, Jacob; Aghi, Manish Kumar
Abstract : INTRODUCTION: The role of adjuvant chemotherapy (AC) in the treatment of low-grade glioma (LGG) has been an area of controversy. While of O6-methylgaunine-DNA-methyltransferase (MGMT) promoter methylation is a predictor of response to AC in high grade glioma, its relevance in LGG is uncertain. METHODS: Overall survival was evaluated using Kaplan-Meier estimates and multivariable Cox proportional hazards regression. Subgroup analyses were conducted in cohorts defined by tumor size, tumor location, histology, extent of resection, and receipt of radiation. RESULTS: Between 2004 and 2018, 1, 139 participants were diagnosed with WHO grade 2 LGG (median [IQR] age, 40 years [31-53]; 578 were male [51%]; 614 were MGMT methylated (54%)). In multivariate analysis, among the 512 patients (45%) receiving AC, there was improved overall survival in methylated compared to unmethylated cohorts (hazard ratio [HR], 0.48; 95% CI, 0.32-0.72; p < 0.001). This association was not demonstrated in patients without AC (HR, 1.01; 95% CI, 0.63-1.60; p=0.985). On subgroup analysis, MGMT methylation status was associated with an independent improved response to chemotherapy in subgroups of patients with no 1p/19q codeletion [astrocytoma], tumor diameter ≥50mml, tumor diameter <50mm, frontal lobe tumors, radiotherapy, no radiotherapy, and subtotal resection MGMT methylation was not associated with improved response to chemotherapy in patients with 1p/19q codeletion [oligodendroglioma] or gross total resection. CONCLUSIONS: MGMT methylation status was associated with response to AC in adult astrocytic LGG, irrespective of treatment with radiation. This relationship was not present for oligodendroglioma. If replicated in contemporary trials, these findings will substantially guide treatment decisions for many LGG patients.